The Influence of Firm Size, Return on Assets, and Debt to Equity Ratio on Bond Ratings with Earnings Management as an Intervening Variable in Financial Companies on the Indonesian Stock Exchange From 2022 to 2024 - Nurhayati, Aisah Dwi; Safitri, Heni; Hariyanto, Dedi (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study aims to examine the influence of firm size, Return on Assets (ROA), and Debt to Equity Ratio (DER) on bond ratings with earnings management as an intervening variable in financial companies listed on the Indonesian Stock Exchange from 2022 to 2024. Bond ratings are crucial for assessing the risk of bond defaults, and understanding the factors that influence these ratings can help companies, investors, and rating agencies make better decisions. Firm size, ROA, and DER have been identified as key financial indicators that affect bond ratings, but the role of earnings management as an intervening factor in this relationship remains underexplored. This study uses a purposive sampling method, focusing on 43 financial companies with investment-grade bond ratings. The data analysis includes financial ratio analysis, path analysis, and several classical assumption tests to ensure the validity of the regression model. The results of this study show that firm size, ROA, and DER do not have a significant direct or indirect influence on bond ratings. The coefficient of determination (R²) indicates that only 5.9% of the variation in bond ratings can be explained by these variables. These findings suggest that factors other than financial ratios, such as macroeconomic conditions or industry stability, may play a more significant role in determining bond ratings. The study recommends further research to explore additional variables and alternative methods for better understanding bond rating dynamics.